Thyroid Function and Metabolic Risk Factors in Obese Youth. Changes during Follow-up: A Preventive Mechanism? - Bouglé, D.; Morello, R.; Brouard, J. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Objectives:  High TSH levels often observed in overweight subjects are associated with metabolic risk. Thyroid hormones which are involved in fat and carbohydrates metabolism are more rarely studied; their blood levels were measured to more precisely explain the relationships between thyroid function and obesity, in healthy overweight youth. This correlation was studied at baseline and during follow-up of some patients.Materials/Methods:  Data collected were BMI and BMI z score, thyroid hormones (TSH, fT4, fT3), fasting blood glucose, HOMA-IR, lipids (triglycerides, HDL and LDL cholesterol), transaminase activity, fibrinogen, leptin, IGF-I; body composition (biphotonic absorptiometry). Data collected in a sample of the group after 6–18 months of medical intervention could also be studied.Results:  At baseline, 13% of the 528 obese subjects (55% girls; 11.3±2.4 years, range 4.1-17.9; BMI z score: 5.4±2.4) had TSH>4mUI/l; fT3 levels were associated with age and transaminase activity; using multivariate regression analysis, with z-score and age as covariates, fT4 showed correlations with TSH, insulin, HOMA IR, blood lipids, and fibrinogen. No correlations were found with leptin, iodine excretion, IGF-I.In 79 patients followed for 52±15 wk (45% girls; age range 8–18.3 years), univariate regression showed a positive correlation between changes in TSH and HOMA-IR, and between changes in fT4 and HDL. Multivariate regression analysis with z score as covariate showed that baseline TSH was associated with negative changes in HOMA-IR.Conclusions:  Increased TSH may be predictive of a decrease in insulin resistance, it should be measured with thyroid hormones; fT4 was associated with a low metabolic risk. Changes in thyroid function could protect against the occurrence of obesity-associated metabolic diseases.
Keywords: obesity; TSH; T4; T3; metabolic syndrome